Two Faces of White Adipose Tissue with Heterogeneous Adipogenic Progenitors - Hwang, Injae (Diabetes Metab J, 2019)
Chronic energy surplus increases body fat, leading to obesity. Since obesity is closely associated with most metabolic complications, pathophysiological roles of adipose tissue in obesity have been intensively studied. White adipose tissue is largely divided into subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT). These two white adipose tissues are similar in their appearance and lipid storage functions. Nonetheless, emerging evidence has suggested that SAT and VAT have different characteristics and functional roles in metabolic regulation. It is likely that there are intrinsic differences between VAT and SAT. In diet-induced obese animal models, it has been reported that adipogenic progenitors in VAT rapidly proliferate and differentiate into adipocytes. In obesity, VAT exhibits elevated inflammatory responses, which are less prevalent in SAT. On the other hand, SAT has metabolically beneficial effects. In this review, we introduce recent studies that focus on cellular and molecular components modulating adipogenesis and immune responses in SAT and VAT. Given that these two fat depots show different functions and characteristics depending on the nutritional status, it is feasible to postulate that SAT and VAT have different developmental origins with distinct adipogenic progenitors, which would be a key determining factor for the response and accommodation to metabolic input for energy homeostasis.